Eight Grade Students’ Mathematics Achievement in TIMSS 2011 Cognitive Domains- A Comparison across Four Southeast Asian Countries - S. Kanageswari Suppiah Shanmugam (SEAMEO Regional Centre for QITEP in Mathematics, 2015)
This article describes secondary data analyses that explores students’ performance in Trends in Mathematics and Science Study (TIMSS) 2011 mathematics items that assess lower order thinking (LOT) and higher order thinking (HOT) in the four participating Southeast Asian countries (Indonesia, Malaysia, Singapore and Thailand). The objectives are to compare the three cognitive domains of knowing, applying and reasoning for these countries, and to study the students’ performance in LOT and HOT items. The analyses were done both qualitatively using document analyses to investigate the cognitive processes incorporated in the education system, and quantitatively using IDB Analyzer to determine students’ performance. The article reports on detailed students’ performance related to the percentage of students at each benchmark and their percentile achievement. The findings reveal that in Indonesia and Thailand, more students were able to answer HOT items, with higher scores than LOT items. For Malaysia, the general student population were able to answer LOT items, with higher scores when compared to HOT items. In Singapore, students at the bottom 25% obtained higher score for LOT items, while the rest performed better on HOT items. However, a higher percentage of students at the weak, intermediate and advanced categories were more able to answer HOT items. The findings seem to suggest that focusing on problem solving may be inadequate. A strategy worth investigating is complementing the infusion of problem solving skills with making mathematical connections to real life situations through non-routine questions. However, more research is required before suggesting any conclusive pedagogical practice.